Antioxidant Therapy in Neonatal Hypoxic Ischemic Encephalopathy: Adjuvant or Future Alternative to Therapeutic Hypothermia? - Veronica Notarbartolo; Bintu Ayla Badiane; Vita Maria Angileri; Ettore Piro; Mario Giuffrè (Metabolites)
Background: Oxidative stress-related diseases in newborns arise from pro-oxidant/antioxidant imbalance in both term and preterm neonates. Pro-oxidant/antioxidant imbalance has shown to be present in different pathological conditions such as hypoxic ischemic encephalopathy (HIE), retinopathy of prematurity (ROP), bronchopulmonary dysplasia (BPD), necrotizing enterocolitis (NEC), and patent ductus arteriosus (PDA). Methods and Results: We performed a narrative review according to the most recent available literature (2012–2024), using Scopus and PubMed as electronic databases. Many observational and experimental studies in vitro and in vivo have evaluated the effectiveness of antioxidant therapies such as melatonin, erythropoietin (EPO), allopurinol, N-acetylcisteine (NAS), and nitric oxide synthase (NOS) inhibitors in these diseases. Perinatal asphyxia is one of the most important causes of mortality and morbidity in term and near-term newborns. Therapeutic hypothermia (TH) is the gold standard treatment for neonates with moderate-severe perinatal asphyxia, resulting in a reduction in the mortality and neurodevelopmental disability rates. Conclusions: According to the most recent literature and clinical trials, melatonin, allopurinol, NAS, NOS inhibitors, magnesium sulfate, and stem cells stand out as promising as both adjuvants and future probable alternatives to TH in the treatment of HIE.